Using betweenness metrics to investigate the geographical distribution of retailers. (October 2021) - Buzzacchi, Luigi; Leveque, Philippe; Taramino, Roberta; Zotteri, Giulio
In retailing, a location's accessibility and attractiveness depends on the spatial distribution of other stores and consumers. In particular, the literature shows that a place is more attractive for retailers if the generic routes taken by consumers often cross it. However, previous studies failed to consider that there are at least two possible consumer routes: job commutes from residential to workplaces and shopping trips among stores. In this paper, we analyze the impact of both consumer routes on the commercial patterns in Turin. The paper demonstrates that daily commutes to workplaces do not benefit a retailer along the trip, as much as journeys for shopping purposes do. In particular, we show that the benefits that a store can have when localized on the routes depend on the kind of goods it sells. Finally, the paper shows that stores selling homogeneous products and stores selling differentiated goods subject to comparison can differently benefit from being located in population hotspots and in commercial areas.